(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article studies the clinical features of the phenomenon of post-stroke depression (PSD) and its impact on the quality of life of patients. During the study, the incidence of affective disorders in patients who have experienced acute cerebral circulation disorders (stroke) and their relationship with the neurotransmitter system were analyzed. It is substantiated that PSD is a major factor that affects not only the psychological state, but also the recovery of cognitive functions and the effectiveness of physical rehabilitation. The article shows that early diagnosis of depression and complex treatment measures (psychopharmacotherapy and cognitive-behavioral therapy) reduce mortality after stroke.